The Changing Face of Military Power - Dorman, A. author. aut Link
XIII, 219 p.
Keywords: With the end of the Cold War, perceptions of the role of armed forces in the international environment changed dramatically and have led to a critical re-evaluation of defence budgets, defence bureaucracies and defence roles. The Changing Face of Military Power brings together some of the most eminent scholars in the field of defence studies to assess the changing dynamics of military power. It focuses in particular on the move towards joint service cooperation as a way of minimising costs and increasing efficiency.